2021
DOI: 10.1101/2021.10.11.21264831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific Detection of Sars-Cov-2 Variants B.1.1.7 (Alpha) and B.1.617.2 (Delta) Using a One-Step Quantitative PCR Assay

Abstract: In this report, we describe the development of an RT-qPCR assay, termed Alpha Delta assay, which can detect SARS-COV-2 (SC-2) and distinguish between the Alpha (B.1.1.7) and Delta (B.1.617.2) variants. The Alpha- and Delta-specific reactions in the assay target mutations that are strongly linked to the target variant. The Alpha reaction targets the D3L substitution in N gene, and the Delta reaction targets the spike gene 156-158 mutations. Additionally, we describe a second Delta-specific assay that we use as … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Variant identification results from sequencing, but such approach faces limitations for application in wastewater with respect to RNA quality and quantity (Lou et al, 2022), but also mathematical tools to deconvolute isolated mutations to reconstruct the original genomes in a mixture of variants (Agrawal et al, 2022b; Jahn et al, 2021; Smyth et al, 2022). Different studies have shown that it is also possible to monitor specific mutations suggestive of VOC to identify the emergence of VOC in a territory and to explain the predominance of certain VOC in epidemic waves (Caduff et al, 2022; Carcereny et al, 2022; Erster et al, 2022; Wurtzer et al, 2022). RT-qPCR approaches require calibration tools for absolute quantification or allelic discrimination (wild-type vs mutated) for relative quantification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variant identification results from sequencing, but such approach faces limitations for application in wastewater with respect to RNA quality and quantity (Lou et al, 2022), but also mathematical tools to deconvolute isolated mutations to reconstruct the original genomes in a mixture of variants (Agrawal et al, 2022b; Jahn et al, 2021; Smyth et al, 2022). Different studies have shown that it is also possible to monitor specific mutations suggestive of VOC to identify the emergence of VOC in a territory and to explain the predominance of certain VOC in epidemic waves (Caduff et al, 2022; Carcereny et al, 2022; Erster et al, 2022; Wurtzer et al, 2022). RT-qPCR approaches require calibration tools for absolute quantification or allelic discrimination (wild-type vs mutated) for relative quantification.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, targeted and specific RT-qPCR approaches have been proposed to detect certain mutations suggestive of variant presence or functional mutations whose evolution could reveal the spread of variants designated as VOC (Wurtzer et al, 2022). Different RT-PCR methods have been proposed based on either relative quantification of mutations to the total SARS-CoV-2 genomes (Erster et al, 2022; Wurtzer et al, 2022; Yaniv et al, 2021), either on wild-type and mutated allelic discrimination (Graber et al, 2021), quantification of mutations and total genomes by digital PCR (Boogaerts et al, 2022; Caduff et al, 2022; Heijnen et al, 2021; Lou et al, 2022). These approaches have been developed and applied to the emergence of Alpha and Delta VOC.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid pace in which SARS-COV-2 (SC-2) variants emerge and spread globally, poses a substantial challenge for efficient surveillance, rendering cell culturing and whole genome sequencing often insufficient for providing fast and reliable data. We previously demonstrated that rapid, affordable and high throughput differentiation between co-circulating SC-2 variants can be accomplished using multiplex quantitative PCR (qPCR), and that this approach can complement and, in some cases, outperform genomic sequencing and similar approaches, for SC-2 variant identification (Erster et al 2021a, Erster et al 2021b). More recently, we reported on the development of qPCR-based assays that specifically identify BA.1 samples and allow straightforward scaling-up for high throughput testing (Erster et al 2022).…”
Section: Introductionmentioning
confidence: 99%